The Mechanism of Tokenization of Currency Values for Modernization of a National Infrastructure of Financial Settlements - Kud, Aleksandr (Pressing Problems of Public Administration, 2024)
The paper substantiates the mechanism of tokenizing currency values to modernize the national financial settlement infrastructure. This necessitated a consistent resolution of three research objectives: a) justifying the existing insurmountable limitations in the widespread adoption of central bank digital currency, particularly in Ukraine; b) clarifying the structure of such a mechanism for using tokenized assets in developing market infrastructure using the e-commerce sector as an example; c) specifying three mandatory legal and technological conditions for the circulation of respective tokenized assets. This article represents a logical and successive stage of the author’s efforts to establish a cycle of new ideas in the scientific domain regarding improving broad access to investment resources and significantly facilitating financial operations through a technologically secure procedure for tokenizing backed assets. The article continues the author’s long-standing series of publications in this area and the closely related field of platform public governance. For the first time, the article proposes a mechanism for using tokenized assets to conduct transactions in the e-commerce and digital commerce sectors with deferred payment without an upfront deposit on the Internet using an escrow account. The core component of the software solution is a digital service based on blockchain technology implemented through a decentralized information platform, e.g., the Ukrainian-originated Bitbon System platform. This service, at least during the stages of acquiring the right to conduct a transaction and its settlement, involves using a bank escrow account. The mechanism employs the methodology of asset tokenization (i.e., with an actual and legal connection to the underlying asset) using an information platform by assigning a unique digital identifier (token) in the distributed ledger of the information platform, subject to maintaining a certain amount of funds in the escrow account. Unlike the project of the Ukrainian central bank digital currency e-hryvnia, implementing the proposed mechanism does not require costly updates to the payment infrastructure in dozens of commercial banks at their own expense, nor does it necessitate additional legislative regulation. At the same time, such a model and mechanism can be used in the legal execution of almost any transaction in terms of ensuring deferred payment under a contract and can be applied in various sectors, including e-commerce, digital commerce, agricultural markets, and others.